PARTISIPASI PEMUDA DALAM MELESTARIKAN KESENIAN RANDAI DI NAGARI BELUBUS KECAMATAN GUGUAK KABUPATEN LIMA PULUH KOTA - Uchy Rahmi Utari; Jasfar Jas; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the participation in preserving Randai art in Nagari Belubus Guguak Subdistrict, Lima Puluh Kota District. The formulation of the problem in this research is how high the participation rate of youth on randai art in Nagari Belubus Guguak Sub-district, Lima Puluh Kota District. After this research is conducted, it is expected to provide benefits to increase knowledge about matters relating to youth participation in preserving randai art by all classes, especially for researchers. This research is descriptive with quantitative approach which aims to describe the result of research with numbers. The sampling technique used simple sample random sampling technique (simple random sampling). Technique of taking data in this research is by technique of inquiry, which amounts to 45 item statement. Data were obtained from 20 respondents for sample and 33 samples for research sample. After the questionnaire was piloted, 5 items were invalid, and the researcher removed all of the invalid statement items. The result of data analysis shows that youth participation in preserving randai arts is moderate with average percentage score 55,204%. This means that youth in nagari belubus have a moderate level of participation. In view of all aspects and can also be concluded that the most dominant is to account for the activities of randai art. Keywords: Participation, Randai